Create, Analyze, and Visualize Phylogenomic Datasets Using PhyloFisher - Jones, Robert E; Tice, Alexander K; Eliáš, Marek; Eme, Laura; Kolísko, Martin; Nenarokov, Serafim; Pánek, Tomáš; Rokas, Antonis; Salomaki, Eric; Strassert, Jürgen F H; Shen, Xing-Xing; Žihala, David; et al. (Current protocols, 2024)
PhyloFisher is a software package written primarily in Python3 that can be used for the creation, analysis, and visualization of phylogenomic datasets that consist of protein sequences from eukaryotic organisms. Unlike many existing phylogenomic pipelines, PhyloFisher comes with a manually curated database of 240 protein-coding genes, a subset of a previous phylogenetic dataset sampled from 304 eukaryotic taxa. The software package can also utilize a user-created database of eukaryotic proteins, which may be more appropriate for shallow evolutionary questions. PhyloFisher is also equipped with a set of utilities to aid in running routine analyses, such as the prediction of alternative genetic codes, removal of genes and/or taxa based on occupancy/completeness of the dataset, testing for amino acid compositional heterogeneity among sequences, removal of heterotachious and/or fast-evolving sites, removal of fast-evolving taxa, supermatrix creation from randomly resampled genes, and supermatrix creation from nucleotide sequences. © 2024 Wiley Periodicals LLC. Basic Protocol 1: Constructing a phylogenomic dataset Basic Protocol 2: Performing phylogenomic analyses Support Protocol 1: Installing PhyloFisher Support Protocol 2: Creating a custom phylogenomic database.
Keywords: aminokyseliny; Amino Acids; genomics; kultura; Biological Evolution; Amino Acid Sequence; transcriptomics; systematics; Phylogeny; Culture; evolution; fylogeneze; biologická evoluce; sekvence aminokyselin